Model of conductivity for perovskites based on the scaling property of grain boundary - Thanh, Phung Quoc; Nhat, Hoang Nam; Cong, Bach Thanh (VNU Journal of Science: Mathematics - Physics; Vol 21 No 4, 2005)
Abstract